Canon and aesthetic value in an authoritarian theory of literature - Ginzburg, Jaime (Revista de Letras, 2007)
This article examines Harold Bloom’s ideas, specially aesthetics autonomy. We also elaborate on the consequences of its diffusion in Brazilian Universities. There is an authoritarian thought in Bloom’s work, associated to an elitist conception of reading.